Young People of the Importance of Healthy Eating and Informing - Grünthal-Drell, Marelle; Veigel, Maarika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Lately, the variety of health -related research conducted in Estonia and elsewhere in the world, has been increased. The proportion of studies about right nutrition has increased especially, which shows that people are more aware and considered about the important link between diet and health. The aim of the research was to find out how young people evaluate their eating habits, what is their expertise in this field and what are the wishes and suggestions from them in relation to the nutrition information. In quantitative research for data collections were used surveys. The sample consisted of 131 young peole, aged 7-26 years.Young people eat mostly unhealthy. This is primarily due to bad habits, which is related to the fast-paced lifestyle. It can be said that the youth nutrition knowledge is good, but implementation in practice is poor.